DC-Link Capacitors Online Condition Monitoring Using Repetitive RLS in Hybrid-Electric Aircraft - Stanislaw Oliszewski; Marcin Pawlak; Mateusz Dybkowski (IEEE Access, 2025)
In the future hybrid-electric aircraft, power distribution systems will play curial role as these would not only provide energy for in-cabin systems but propulsion as well. In the turboelectric architecture of these airplanes ac/dc/ac converters are present. DC-link capacitors, that are part of the voltage converters, have high percentage of faults occurring among power electronics. As reliability is important in the aviation industry, condition monitoring of DC-link is required. Different types of capacitors may be used in the future hybrid-electric aircraft power converters. DC-link voltage circuit capacitors are key elements of power electronic systems and are subject to aging and damage processes. It is therefore important to conduct permanent diagnostic and quickly detect any anomaly in the DC circuit. Among the most popular signals in diagnostic process, capacitance drop is a common degradation indicator. In order to estimate the DC-link capacitance, repetitive recursive least squares (RRLS) method was developed. The proposed capacitor health monitoring algorithm has low complexity and operates on data that has size constraints. Such solutions are extremely important in aviation systems, where there are large limitations in the amount of data transmitted by the control bus. The proposed capacitor capacitance estimation algorithm was verified in a simulation environment and on a test bench, where it is possible to simulate capacitor degradation processes. Strict aviation requirements were applied regarding the amount of data and the speed of the algorithm. Range of different capacitance values and datasets were taken into consideration. Results obtained provide information on what type of DC-link capacitors can be monitored using RRLS.